The Influence of Entrepreneurship Education and Entrepreneurial Orientation on Entrepreneurial Intention Through Locus of Control in Public High School Students in Mojokerto District - Amenah, Amenah; Kusdyanti, Heny; Wardana, Ludi Wisnu (PT. EQUATOR SINAR AKADEMIA, 2024)
This study intends to explore more deeply the effect of entrepreneurship education and entrepreneurial orientation of vocational students on entrepreneurial intentions with mediated locus of control, especially in private vocational students in Mojokerto Regency. This study uses an explanatory research design with a quantitative description analysis approach. The sample in this study was 250 students of private SMK students in the Mojokerto district and data analysis was conducted by Partial Least Square (PLS) method. The results showed that there is a direct effect of entrepreneurship education on locus of control, there is a direct effect of entrepreneurial orientation on locus of control, there is a direct effect of entrepreneurship education on entrepreneurial intention, there is a direct effect of entrepreneurial orientation on entrepreneurial intention, there is a direct effect of locus of control on entrepreneurial intention, there is an indirect effect of entrepreneurship education on entrepreneurial intention through locus of control, there is an indirect effect of entrepreneurial orientation on entrepreneurial intention through locus of control